The Current Account Income Balance : External Adjustment Channel or Vulnerability Amplifier? - Behar, Alberto (IMF Working Papers; Working Paper ;, 2022)
In terms of size, the net income balance (IB) is comparable to the trade balance (TB) for many countries. Yet the role of the IB in mitigating external vulnerabilities or complicating external adjustment remains underexplored. This paper studies the role of the IB in stabilizing or destabilizing the current account over the cycle and in crises. Our results show that, due to a negative correlation with the TB, the IB significantly dampens the time series volatility of the current account for most countries. However, the IB generally does not improve during crisis episodes, so current account adjustment occurs entirely through improvements in the TB. The paper also estimates IB semi-elasticities with respect to the exchange rate (ER). Semi-elasticities are small for most countries, so the IB is generally not a significant channel through which the ER stabilizes the current account, and trade-based semi-elasticities are, with some important exceptions, good proxies for current account semi-elasticities used in external sector assessments.